Injuries Presenting to a Walk-in Clinic at a Summer Dance Intensive Program: A Three-Year Retrospective Data Analysis. Issue 3 (September 2014) - Fulton, Jessica; Burgi, Ciara; Canizares, Rosalinda C.; Sheets, Charles; Butler, Robert J.
Summer dance intensive programs are an integral part of many serious dancers' training. The risk and rate of injury in this setting have not been well studied. The goal of this data analysis is to detail the epidemiology of dance injuries reported during a summer dance intensive over a consecutive 3 year period. Data collection included information regarding the number of evaluation and treatment sessions conducted at the program's walk-in clinic, body regions injured, whether the injuries were recurrences of pre-existing conditions or newly sustained during the intensive, and at what point in the program they were recorded. Overall, more of the clinic's clientele presented with multiple injuries than with single discrete injuries. The anatomic distribution of injuries appears to be consistent with previously reported data, with the four most commonly injured body regions being ankle, pelvis and hip, knee, and lumbar spine. Injuries sustained during the intensive (IR) occurred at a 2:1 ratio to pre-intensive injuries (PR). Relative to those with PR injuries, dancers with IR injuries were far more likely to present during the first half of the program. This study is a first step toward filling a gap in the literature by describing injury incidence in a specific population within the dance community.